From Awareness to Acceptance: Quantitative Evidence on the Public Readiness Toward the Global Unified Hijri Calendar - Mursyid Fikri; Muh Fauzi Anas (Hikmatuna : Journal for Integrative Islamic Studies, 2025)
Unity in determining the Hijri month’s beginning remains a significant issue in the Muslim world, including Indonesia. Muhammadiyah has proposed the Single Global Hijri Calendar (KHGT) as a scientific and integrative solution to standardize Islamic dates worldwide. This study aims to measure the levels of awareness, understanding, acceptance, and readiness of Indonesian Muslims toward the KHGT initiative. Using a descriptive-quantitative approach, data were collected from 300 online respondents via a Likert-scale questionnaire and analysed using descriptive statistics and Pearson's correlation analysis. The results show that all indicators fall within the high category: awareness (3.96), understanding (3.83), acceptance (4.32), and readiness (4.20). The correlation results between variables are significant and positive, with the strongest relationship found between awareness and understanding (r = 0.865). These findings indicate that higher awareness and understanding contribute to greater public acceptance of and readiness to adopt the KHGT. However, the dominance of Muhammadiyah respondents (88.9%) highlights the need for broader cross-organizational outreach. This study provides empirical evidence supporting the diffusion of religious innovations and underscores the importance of communication strategies that combine scientific education and cultural da’wah to promote the global adoption of the KHGT.